A predictive approach to integrating connectivity into landscape scale protected areas planning - Paul O’Brien; Natasha Carr; Jeff Bowman (PLoS ONE, 2026)
It has been recognized that protecting at least 30% of terrestrial lands by 2030 (30x30) in systems of well-connected protected areas will be necessary for halting global biodiversity loss. While significant effort has been made to increase the coverage of global protected areas, connectivity has been found to fall short of what is needed to maintain proper ecological function. We present methods to explicitly incorporate connectivity into planning of future protected areas, using the protected area network in Ontario, Canada as a case study. We first carried out a series of connectivity analyses with simulated, generic parks, and estimated the effect of each new park on network connectivity. We then built and evaluated a set of regression models to determine characteristics of these generic parks that are predictors of optimal protected area placement for improving network connectivity. We found that in all cases, adding a generic park resulted in improved network connectivity; however, some park placements lead to greater improvements. The top model suggested that protected areas should have the greatest benefit to connectivity of the network when they have a low edge-to-area ratio, are close to the center of the landscape and to a network node, have a low degree of internal anthropogenic influence, but a close proximity to developed landscapes. We demonstrated an application of this approach by using the model to prioritize an independent set of candidate parks by their predicted benefit to network connectivity. The resulting model provides a tool with which Indigenous communities, land trust managers, and protected area planners can evaluate and prioritize candidate sites based on their expected benefit to improving connectivity of a given protected area network. As efforts to increase area-based conservation are ramped up to help meet national 30x30 targets, this should be an important tool for ensuring connectivity is explicitly incorporated into protected areas planning.